2017
DOI: 10.1111/wrr.12547
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of skeletal muscle after volumetric muscle loss

Abstract: Volumetric muscle loss (VML), usually occurring following traumatic injury, results in a composite loss of muscle mass. These injuries manifest as decreased strength and functional impairments. Clinically, these injuries often heal with fibrosis, as opposed to skeletal muscle regeneration. This study examines the healing patterns of a skeletal muscle following VML in a murine model. Eight-week old male C57BL/6J mice used in the study underwent either bilateral VML injury or cryoinjury, a widely used model know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…coordination of the inflammatory response, fibrotic response and myogenesis for optimal growth and repair. Chronic inflammation is associated with VML (Nuutila et al, 2017) and increased gene expression of inflammatory modulators have been reported at various time points following VML (Corona et al 2018). Our laboratory has demonstrated elevated expression of inflammatory cytokines TGF-β and interleukin (IL)-1β following VML (Kim et al, 2020).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…coordination of the inflammatory response, fibrotic response and myogenesis for optimal growth and repair. Chronic inflammation is associated with VML (Nuutila et al, 2017) and increased gene expression of inflammatory modulators have been reported at various time points following VML (Corona et al 2018). Our laboratory has demonstrated elevated expression of inflammatory cytokines TGF-β and interleukin (IL)-1β following VML (Kim et al, 2020).…”
mentioning
confidence: 88%
“…Skeletal muscle regeneration is a process that is highly regulated and involves coordination of the inflammatory response, fibrotic response and myogenesis for optimal growth and repair. Chronic inflammation is associated with VML (Nuutila et al., 2017) and increased gene expression of inflammatory modulators have been reported at various time points following VML (Corona et al. 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[2] However, when a large proportion of mass is lost within a given muscle, as the result of a trauma, disease, or surgical ablation, the native regenerative capabilities of muscle become overwhelmed. [3,4] Instead, skeletal muscle heals with an overactive fibrotic response to volumetric muscle loss (VML) that results in disabling scar tissue. [5] Such injuries are frequent and impose an economic impact on the order of billions of dollars annually.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the literature on the effects of COX inhibition on skeletal muscle regeneration has been conducted in recoverable injury models (Almekinders & Gilbert, 1986; Bondesen, Mills, Kegley, & Pavlath, 2004; Bondesen, Mills, & Pavlath, 2006; Mishra, Friden, Schmitz, & Lieber, 1995; Obremsky, Seaber, Ribbeck, Garrett, & JR., 1994; Thorsson, Rantanen, Hurme, & Kalimo, 1998) that can be characterized by a well‐orchestrated interplay between the immune and myogenic progenitor cells, which infiltrate the zone of injury. This is definitively not the case for VML as numerous reports have shown (Aguilar et al, 2018, Corona et al, 2017a; Greising et al, 2017b; Nuutila et al, 2017). As such, one might postulate that any positive effects of COX inhibition on inflammation and skeletal muscle regeneration are simply overwhelmed by the magnitude of the immune‐inflammatory response to the VML injury.…”
Section: Discussionmentioning
confidence: 84%